O uso de materiais lúdicos na educação de surdos: reflexões, escolhas e uso por professores surdos - Lopes, Sandra Guilherma Lira (Brasil, 2024)
The use of ludic material is a resource that helps school subjects and transforms traditional teaching, enriching skills and developing the deaf student's ability to perceive knowledge. This work aims to present the approaches to contributions and the benefits that playful material provides in cognitive development, aiming to encourage deaf students to participate and debate different topics through games and play within the school environment. We have as authors bibliographic reference this research: Yvette Dartner, Tizuco Kishimoto, Cibele Pinto and Helenice Tavares, Brazil, Clarita Almeida and Helenice Tavares, LDB, Tânia Sampaio, Eduardo Córdula, Ana Carvalho, Lucia Pereira, Sofia Freire, and Paulo Almeida. The objective was to understand the importance of the use of playful material within the classroom by deaf teachers, and specifically: a) to understand the concepts of playfulness, playfulness and playful materials; b) to interview deaf teachers who work in schools for the deaf in Manaus; c) to demonstrate how deaf teachers use ludic materials to encourage the learning of deaf students in the classroom and in different school contexts. The methodology used was the qualitative approach, through case study, through bibliographic review (articles, scientific journals, books and legislation) and field research, applying a semi-structured interview with the participation of two deaf teachers in which they pointed out important information for research on teaching, ludic material, the perception of the teacher's view of the student to have an interest in classes and see their development in daily practices.